(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This study examines the directions for increasing the investment activity of jointstock companies in the context of economic reforms. It focuses on the role of financial markets, institutional investors, and corporate governance in enhancing investment performance. The research highlights that effective economic reforms, including market liberalization and improved regulatory frameworks, create favorable conditions for investment growth. The findings suggest that a comprehensive approach combining financial, institutional, and managerial factors is essential for strengthening investment activity and ensuring sustainable economic development